2020
DOI: 10.1590/1806-9061-2020-1310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Frying Fat, Vegetable Oil and Calcium Soaps Of Palm Oil on the Productive Behavior and Carcass Yield of Broiler Chickens

Abstract: Vegetable oils (VO) and animal fats are conventional lipid sources used in feed formulations. Frying fats (FF) and calcium soaps of palm oil (CaSPO) are low-cost lipid sources. This study evaluated the productive performance of broiler chickens fed diets with CaSPO in substitution for VO or FF. Two hundred, 1-day old male broiler chickens were allocated in a randomized design with factorial arrangement ( 22). Diets included 2 lipid sources (FF and VO) and 2 CaSPO levels (0 and 50%). The study had two phases (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…However, the final live weight was not influenced by CasPO level in the diet. In our previous work (Villanueva-Lopez et al, 2020), we reported similar productive performance in broiler chickens fed diets in which vegetable oil or recycled fats were replaced with CaSPO. We concluded that CaSPO represents an alternative to partially replace conventional vegetable oils (VO) in diets for broiler chickens, particularly in countries where CaSPO are cheaper than traditional VO; however, reports on this topic are very limited.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…However, the final live weight was not influenced by CasPO level in the diet. In our previous work (Villanueva-Lopez et al, 2020), we reported similar productive performance in broiler chickens fed diets in which vegetable oil or recycled fats were replaced with CaSPO. We concluded that CaSPO represents an alternative to partially replace conventional vegetable oils (VO) in diets for broiler chickens, particularly in countries where CaSPO are cheaper than traditional VO; however, reports on this topic are very limited.…”
Section: Introductionmentioning
confidence: 57%
“…The inclusion of CaSPO in diets reduced broiler chickens' body weight gain and carcass weight. In contrast, Villanueva-Lopez et al (2020) reported beneficial effects of dietary CaSPO on the breast yield of broiler chickens. As previously mentioned, recycled fats were used , in the study of Villanueva-Lopez et al (2020), whereas this type of fats was not used in the present study.…”
Section: Carcass Characteristicsmentioning
confidence: 89%
See 2 more Smart Citations
“…The use of vegetable oils and/or animal fat is essential in formulating poultry diets, as these sources help to achieve ideal levels of metabolizable energy (Villanueva-Lopez et al, 2020). Due to the high demand and diversified use of vegetable oils, not only for animal but also human use, the world market has faced difficulties in producing high quantities to supply these chains.…”
Section: Introductionmentioning
confidence: 99%